Multiple oral verruciform xanthomas: A rare entity - Jayati Shailesh Dave; Sunanda Arun Mahajan; Atul M Dongre; Meghana Rane (Wolters Kluwer Medknow Publications, 2020)
Verruciform xanthoma (VX) is an uncommon benign lesion that can affect oral, genital mucosa, and rarely skin. The characteristic foam cells seen in papillary dermis are a hallmark for diagnosing this entity. A 42-year-old male, tobacco-chewer presented with asymptomatic white-circular plaques on the bilateral buccal mucosa and yellow papules on retromolar area which on histopathological evaluation showed parakeratotic epithelium with surface and deep invagination of columns of parakeratosis throughout the hyperplastic epidermis, few neutrophils in upper spinous layers, and uniform elongation of rete ridges. The rete ridges showed numerous lipid-laden CD 68-positive foam cells. Punch excision coupled with cryotherapy was done, which resulted in the complete resolution of lesions. We publish this uncommon benign entity for increased awareness among physicians to consider it as a differential of verrucous lesion in the mucosa. Our patient had two different morphology of lesions, both suggestive of VX with characteristic foam cells on histopathology.